THE LOCAL CURRICULUM ADMINISTRATION ON PARTICIPATION OF EDUCATIONAL INSTITUTIONS IN HUASAI NETWORK 1 UNDER NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Chanthong, Khanittha; PhrakruSumethpariyatikul; Srisuwan, Kasama (Journal of Educational Review Faculty of Education in MCU, 2025)
This research aims to 1) study the local curriculum administration of educational institutions in Huasai network 1. 2) study the approach to participatory local curriculum administration of educational institutions in Huasai network 1. 3) present the approach to participatory local curriculum administration of educational institutions in Huasai network 1 under Nakhon Si Thammarat Primary Educational Service Area Office 3.This study employs a qualitative research approach, collecting data through in-depth interviews with 15 stakeholders, expert interviews with 5 specialists to draft an approach, and focus group discussions with 7 experts to assess feasibility, appropriateness, and benefits. The qualitative data were analyzed using content analysis. The findings revealed that: 1) the local curriculum administration of educational institutions in Huasai network 1. The administration of the local curriculum involves the appointment of appropriate personnel, both internal and external, to oversee its implementation. The academic head teacher serves as the primary responsible person, while schoolteachers actively participate in the process. However, the basic data collected for curriculum development is limited to a small group of informants, which does not adequately reflect the trends and changes within the community. As a result, the content of the local curriculum does not align with the current transformations in the community. Additionally, some teachers lack the necessary knowledge and skills in curriculum design. Moreover, the community has minimal involvement in both the development and implementation of the local curriculum in the learning process. Although the curriculum is assessed by the group of teachers responsible for its development, the process of curriculum improvement and refinement lacks continuity and systematic implementation. 2) the approach to participatory local curriculum administration of educational institutions in Huasai network 1 under Nakhon Si Thammarat Primary Educational Service Area Office 3, consists of six key steps: 1. appointment 2. analysis 3. development 4. implementation 5. evaluation 6. revision, Effective implementation requires the collaboration of school administrators, teachers, and the community through a structured and continuous participatory process, which includes: 1. Participation in decision-making. 2. Participation in implementation. 3. Participation in benefits. 4. Participation in evaluation. And 3) the approach to participatory local curriculum administration of educational institutions in Huasai network 1 under Nakhon Si Thammarat Primary Educational Service Area Office 3. was found to be feasible, appropriate, and beneficial for the actual implementation of participatory local curriculum administration in schools.